Islamic Corporate Governance sebagai Moderasi: Pengaruh Dividend Per Share, Managerial Ownership dan Struktur Modal terhadap Stock Price : (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Indeks Saham Syariah Indonesia (ISSI) Periode 2020-2023 - Hamidatul Khoiriyah; Yusvita Nena Arinta (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2025)
This research aims to analyze and know the effect of dividend per share, managerial ownership and capital structure variables on stock price and the role of Islamic corporate governance as a moderating variable. This research uses a quantitative approach with panel data obtained from the secondary data of each company's annual report, the sample in this research amounted to 46 companies that fit the criteria multiplied by 4 years of observation so that a population of 184 manufacturing companies listed on the Indonesian Sharia Stock Index for the period 2020-2023 was obtained, with the Eviews 12 tool, The results obtained dividends per share and managerial ownership have a positive and significant effect on stock price, while capital structure has a negative and insignificant effect on stock price. The moderating role of Islamic corporate governance is able to moderate the effect of dividend per share and managerial ownership on stock price but is unable to moderate capital structure on stock price.